DOI: 10.11606/t.64.2008.tde-17092008-144314
|View full text |Cite
|
Sign up to set email alerts
|

Aumento da vida útil de cogumelos Pleurotus sajor-caju in natura com aplicação de radiação gama

Abstract: Sensory analyses showed that the control had higher scores for color, aroma and appearance attributes; they were above the acceptability limit until the last storage day. In general, the irradiated samples were accepted for the evaluated attributes until the 5 th storage day; thus, establishing the shelf-life for irradiated mushrooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
2

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
1
6
1
2
Order By: Relevance
“…PB-1 had the highest average of crude protein (28.9%) (Figure 7) There was effect of irradiation on the crude protein content of the mushrooms (Figure 8), and the dose of 500 Gy provided the highest average (27.5%), when compared to those of the control group (26.1%). Different results were obtained by Moda (2008), who found that irradiation did not affect the crude protein content of Pleurotus sajor-caju.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…PB-1 had the highest average of crude protein (28.9%) (Figure 7) There was effect of irradiation on the crude protein content of the mushrooms (Figure 8), and the dose of 500 Gy provided the highest average (27.5%), when compared to those of the control group (26.1%). Different results were obtained by Moda (2008), who found that irradiation did not affect the crude protein content of Pleurotus sajor-caju.…”
Section: Resultsmentioning
confidence: 67%
“…Different results were obtained by Moda (2008) with P. sajor-caju, whose average crude fiber was not influenced by the irradiation dose on the 1 st day of storage.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…However, it is known that such solutions change the original taste of fresh mushrooms and their physicochemical and sensory properties. Recently, Moda (2008) evaluated the shelf life of Pleurotus sajor-caju irradiated with 125, 250, 500, and 750 Gy and found that a dose of 750 Gy was the most suitable and its estimated shelf life of five days, being this time superior for nonirradiated mushrooms. However, in Brazil, no scientific reports were published of the use of gamma radiation to A. bisporus, being necessary to check the feasibility of applying this technique in growing conditions prevailing in the country.…”
Section: Introductionmentioning
confidence: 99%